Role and Prospects of Engineering in Nanotechnology: An Overview - Dr.Ruma Arora; Manish Gome (Peneliti Teknologi Teknik Indonesia, 2023)
Background - The rapid growth of digital technology has resulted in an enormous rise in computing activities, imposing strict requirements on next-generation computing for energy efficiency and area efficiency. For matrix and logic computing, new technologies such as in-memory computing and transistor-based computing have emerged to accommodate the increasing data need. Nanocomputers - However, in order to meet the demands of the future, new materials are desperately required. In order to expand the range of electronic devices and their applications, new technologies must be created, such as Si complementary metal–oxide–semiconductor technology. Since two-dimensional materials have a wide range of electrical characteristics, they have the potential to improve computation efficiency while allowing further device downscaling. Conclusion - Paper covers the challenges, pitfalls, and potential applications of integrating nanotechnology and computer science in this overview.